Identification and Validation of Circadian Rhythm‐Related Genes Involved in Intervertebral Disc Degeneration and Analysis of Immune Cell Infiltration via Machine Learning - Yongbo Zhang; Liuyang Chen; Sheng Yang; Rui Dai; Hua Sun; Liang Zhang (JOR Spine, 2025)
ABSTRACT Background Low back pain is a significant burden worldwide, and intervertebral disc degeneration (IVDD) is identified as the primary cause. Recent research has emphasized the significant role of circadian rhythms (CRs) and immunity in affecting intervertebral discs (IVD). However, the influence of circadian rhythms and immunity on the mechanism of IVDD remains unclear. This study aimed to identify and validate key rhythm‐related genes in IVDD and analyze their correlation with immune cell infiltration. Methods Two gene expression profiles related to IVDD and rhythm‐related genes were obtained from the Gene Expression Omnibus and GeneCards databases to identify differentially expressed rhythm‐related genes (DERGs). Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene set enrichment analysis (GSEA) were conducted to explore the biological functions of these genes. LASSO regression and SVM algorithms were employed to identify hub genes. We subsequently investigated the correlation between hub rhythm‐related genes and immune cell infiltration. Finally, nucleus pulposus‐derived mesenchymal stem cells (NPMSCs) were isolated from normal and degenerative human IVD tissues. Hub rhythm‐related genes expression in NPMSCs was confirmed by real‐time quantitative PCR (RT‐qPCR). Results Six hub genes related to CRs (CCND1, FOXO1, FRMD8, NTRK2, PRRT1, and TFPI) were screened out. Immune infiltration analysis revealed that the IVDD group had significantly more M0 macrophages and significantly fewer follicular helper T cells than those of the control group. Specifically, M0 macrophages were significantly associated with FRMD8, PRRT1, and TFPI. T follicular helper cells were significantly associated with FRDM8, FOXO1, and CCND1. We further confirmed that CCND1, FRMD8, NTRK2, and TFPI were dysrhythmic within NPMSCs from degenerated IVD in vitro. Conclusion Six genes (CCND1, FOXO1, FRMD8, NTRK2, PRRT1 and TFPI) linked to circadian rhythms associated with IVDD progression, together with immunity. The identification of these DEGs may provide new insights for the diagnosis and treatment of IVDD.